From Hai Yao, Yang Yao to Xi Yao: Sinification of Material Medical from the West - Patrick Chiu (Wolters Kluwer Health/LWW, 2023)
In ancient China, Daoist philosophers developed the concepts of qi (energy), Wu Xing (five elements), and yin (feminine, dark, negative) and yang (masculine, bright, positive) opposite forces between 200 and 600 BCE. Based on these philosophies, Zhen Jiu (acupuncture), Ben Cao (materia medica), and the practice of Qi Gong (energy optimization movements) evolved as the three interrelated therapeutic regimens of Chinese medicine (Note 1). Since the time of Zhang Qian, who discovered China's western regions in the 1st century BCE, Hai Yao (the exotic elements of materia medica from the maritime Silk Road countries), had been transmitted from the ancient land and maritime routes of the Silk Road to China in the past two millennia (Note 2). Since the late 17th century, the English East India Company, later called the British East India Company, introduced Yang Yao (opium) to the Manchu Qing Empire to balance a growing trade deficit for tea export from China to the British Empire. After the First Opium War ended in 1842, enterprising expatriate chemists and druggists in the treaty ports imported Xi Yao (modern medicines from the Western world) for sale to the merchant navy and the local market. From the second half of the 19th century onwards, both Hai Yao and Xi Yao have become a fully integrated part of modern China's armamentarium for the Chinese medicine and Western hospitals and retail pharmacy sectors. This paper articulates the journey of adoption of exotic elements of materia medica from the ancient land and sea routes of the Silk Road, including the western regions and the rest of the world in the past two millennia. Opium traders, ship surgeons, medical and pharmaceutical missionaries, enterprising traders, and policymakers together transformed Ben Cao into Xi Yao during the late Manchu Qing dynasty and the early Nationalist Era.